2013
DOI: 10.1253/circj.cj-12-0011
|View full text |Cite
|
Sign up to set email alerts
|

Serial Changes in Glucose-Loaded <sup>18</sup>F-Fluoro-2-Deoxyglucose Positron Emission Tomography, <sup>99m</sup>Tc-Tetrofosmin and <sup>123</sup>I-Beta-Methyl-p-Iodophenyl-Penta-Decanoic Acid Myocardial Single-Photon Emission Computed Tomography Images in Patients With Anterior Acute Myocardial Infarction

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp he energy metabolism of the heart and the utilization of substrates including glucose, fatty acids, amino acids, lactic acid and ketone bodies depend on circumstances, 1 and are primarily based on fatty acid metabolism and glucose metabolism in a competitive manner. 2 However, a shift to anaerobic metabolism because of low oxygen supplies causes ischemic myocardium to primarily utilize glucose. 3,4 Many reports ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…9 This phenomenon is based more on severely damaged fatty acid metabolism as "ischemic memory" than upon perfusion injury caused by myocardial ischemia. 10, 11 The uptake of BMIPP was found to be more impaired than that of the myocardial perfusion tracer, thallium-201 (TL) in patients with CS, 12 but only a low number of patients were assessed in that study.…”
Section: Discussionmentioning
confidence: 93%
“…9 This phenomenon is based more on severely damaged fatty acid metabolism as "ischemic memory" than upon perfusion injury caused by myocardial ischemia. 10, 11 The uptake of BMIPP was found to be more impaired than that of the myocardial perfusion tracer, thallium-201 (TL) in patients with CS, 12 but only a low number of patients were assessed in that study.…”
Section: Discussionmentioning
confidence: 93%
“…As such, PCI should be reserved for symptomatic patients with positive angina symptoms while on optimal doses of guideline-recommended medical therapy [41]. Our literature review found a large body of studies where patients referred for viability imaging with PET were subjected to PCI [22,38,[42][43][44][45][46][47][48][49][50].…”
Section: Different Myocardial Revascularisation Strategies Usedmentioning
confidence: 99%
“…2 In particular, the size of the defect on FDG is considerably larger in the acute than the chronic phase. Others have reported similar findings.…”
Section: Article P 137mentioning
confidence: 99%